Key player - Yang, Kelly (Yang, Kelly. Front desk novel, 2022)
With her spot at journalism camp in jeopardy because of a low grade in physical education class, Mia Tang decides she'll raise her grade by writing a paper based on interviews with professional U.S. and Chinese soccer players competing in the World Cup finals being hosted in Pasadena. However, securing interviews with the players turns out to be harder than she thought. Fortunately, Mia doesn't easily give up.